Manometry based randomised trial of endoscopic sphincterotomy for sphincter of Oddi dysfunction. Issue 1 (1st January 2000) - Toouli, J; Roberts-Thomson, I C; Kellow, J; Dowsett, J; Saccone, G T P; Evans, P; Jeans, P; Cox, M; Anderson, P; Worthley, C; Chan, Y; Shanks, N; et al.
Abstract : BACKGROUND: Endoscopic sphincterotomy for biliary-type pain after cholecystectomy remains controversial despite evidence of efficacy in some patients with a high sphincter of Oddi (SO) basal pressure (SO stenosis). AIM: To evaluate the effects of sphincterotomy in patients randomised on the basis of results from endoscopic biliary manometry. METHODS: Endoscopic biliary manometry was performed in 81 patients with biliary-type pain after cholecystectomy who had a dilated bile duct on retrograde cholangiography, transient increases in liver enzymes after episodes of pain, or positive responses to challenge with morphine/neostigmine. The manometric record was categorised as SO stenosis, SO dyskinesia, or normal, after which the patient was randomised in each category to sphincterotomy or to a sham procedure in a prospective double blind study. Symptoms were assessed at intervals of three months for 24 months by an independent observer, and the effects of sphincterotomy on sphincter function were monitored by repeat manometry after three and 24 months. RESULTS: In the SO stenosis group, symptoms improved in 11 of 13 patients treated by sphincterotomy and in five of 13 subjected to a sham procedure (p = 0.041). When manometric records were categorised as dyskinesia or normal, results from sphincterotomy and sham procedures did not differ. Complications were rare, but included mild pancreatitis in seven patients (14 episodes) and a collection in the right upper quadrant, presumably related to a minor perforation. At three months, the endoscopic incision was extended in 19 patients because of manometric evidence of incomplete division of the sphincter. CONCLUSION: In patients with presumed SO dysfunction, endoscopic sphincterotomy is helpful in those with manometric features of SO stenosis.